2011
DOI: 10.1080/02642069.2011.559226
|View full text |Cite
|
Sign up to set email alerts
|

Exploring working conditions as determinants of job satisfaction: an empirical test among Catalonia service workers

Abstract: Job satisfaction is particularly important in the service industry since it involves direct contact with customers and thus has a direct influence on company performance. We analyzed the impact of ten working conditions on job satisfaction by means of structural equation modelling in a representative stratified random sample of 1553 service sector employees in Catalonia (Spain). We found significant effects in social aspects (recognition of a job well done and social support), followed by psychologica l loads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 77 publications
0
6
0
3
Order By: Relevance
“…The organizational living environment influences construction labour satisfaction because labourers want a living environment that provides greater physical comfort and reliable lifestyle support and hence promotes work productivity (Turkyilmaz et al 2011). Some studies have shown that low job satisfaction levels can mainly be attributed to poor life environment (Marin-García et al 2011). Therefore, the following hypothesis is formulated.…”
Section: Managerial Drivers Satisfaction and Loyaltymentioning
confidence: 99%
“…The organizational living environment influences construction labour satisfaction because labourers want a living environment that provides greater physical comfort and reliable lifestyle support and hence promotes work productivity (Turkyilmaz et al 2011). Some studies have shown that low job satisfaction levels can mainly be attributed to poor life environment (Marin-García et al 2011). Therefore, the following hypothesis is formulated.…”
Section: Managerial Drivers Satisfaction and Loyaltymentioning
confidence: 99%
“…There is no agreement on the best way to measure satisfaction. There are several arguments for and against single item or multi-scale/multi-item (Bergkvist & Rossiter, 2007;Hernández Maestro, Muñoz Gallego & Santos Requejo, 2008;Oshagbemi, 1999;Marin-Garcia, Bonavia & Losilla, 2011). On the one hand, single-item scales occupy less space, are less expensive and may be a better measure of job satisfaction change, while the multi-item scales provide more information on the facets of satisfaction, and can be determined their reliability and validity (Nagy, 2002).…”
Section: Msqmentioning
confidence: 99%
“…La satisfacción ha sido estudiada tanto como una medida multidimensional (Locke, 1976;Weiss, Dawis, England & Lofquist, 1967;Smith, Kendall & Hullin, 1969;Spector et al, 2007;Meliá, Pradilla, Martí, Sancerni, Oliver & Tomás, 1990;Hackman & Oldham, 1976;Hartman & Schmidt, 1995;Elliott & Shin, 2002;Harvey, 1995;Coffey & Gibbs, 2001;Alves & Raposo, 2009), como unidimensional (Hsu & Wang, 2008;Roelen, Koopmans & Groothoff, 2008;De Jonge, Dormann, Janssen, Dollard, Landeweerd & Nijhuis, 2001;Hair, Hult, Ringle & Sarstedt, 2013;Giraldo-O'Meara, Marín-García & Martínez-Gómez, 2014;Oshagbemi, 1999;Bergkvist & Rossiter, 2007;Petrescu & Simmons, 2008;Marín-García, Bonavia & Losilla, 2011). Varios autores han tratado de determinar los factores que están relacionados con la satisfacción.…”
Section: Cómo Medir La Satisfacción De Los Estudiantesunclassified